1993
DOI: 10.1007/bf02246979
|View full text |Cite
|
Sign up to set email alerts
|

Platelet 5-HT uptake sites in depression: three concurrent measures using [3H] imipramine and [3H] paroxetine

Abstract: Platelet 5-HT uptake sites were measured in 40 depressed patients and 40 controls using [3H] imipramine binding, defined with desmethylimipramine (DMI) and Na+ dependence, and [3H] paroxetine binding. In control subjects the Bmax of DMI defined [3H] imipramine binding was significantly higher than both Na+ dependent [3H] imipramine (by 30%) and [3H] paroxetine binding (by 22%). The Bmax of Na+ dependent [3H] imipramine and [3H] paroxetine binding did not differ significantly. The Kd of Na+ dependent [3H] imipr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

1994
1994
2000
2000

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(16 citation statements)
references
References 18 publications
2
14
0
Order By: Relevance
“…These findings have subsequently been replicated in many, but not all, studies and have become one of the most reproducible findings in the biology of affective illness (D'Haenen et al, 1988;Langer and Galzin, 1988;Nemeroff et al, 1988Nemeroff et al, , 1994Elliot, 1991;Lawrence et al, 1993;DeMet and Chicz-DeMet, 1996). Recently, a meta-analysis of these data revealed a highly significant reduction in platelet SERT density in drug-free depressed patients (Ellis and Salmond, 1994).…”
Section: H]-citalopram and [mentioning
confidence: 80%
“…These findings have subsequently been replicated in many, but not all, studies and have become one of the most reproducible findings in the biology of affective illness (D'Haenen et al, 1988;Langer and Galzin, 1988;Nemeroff et al, 1988Nemeroff et al, , 1994Elliot, 1991;Lawrence et al, 1993;DeMet and Chicz-DeMet, 1996). Recently, a meta-analysis of these data revealed a highly significant reduction in platelet SERT density in drug-free depressed patients (Ellis and Salmond, 1994).…”
Section: H]-citalopram and [mentioning
confidence: 80%
“…One study has found decreased 5HT 1A density in hippocampus and amygdala [Cheetham et al, 1991], as opposed to increased density in cortex [Matsubara et al, 1991], suggesting differential regulation between limbic and cortical systems. Further evidence for abnormalities in 5HT transmission are the findings of reduced serotonin transporter binding in post-mortem cortex [Leake et al, 1991], though this has not been consistently found [Lawrence, 1993]. A more consistent finding has been reduced serotonin uptake and reduced serotonin transporter binding in platelets [Kaplan and Mann, 1982;Nemeroff, 1988;Owens and Nemeroff, 1994] and more recently in brain [Malison et al, 1998].…”
Section: Ht Alterations In Depression and Anxiety Disordersmentioning
confidence: 94%
“…In fact patients with depression [30,31] and social phobia [32] have been reported to have a normal binding, while controversial data exist for patients with panic disorder [33,34]. This is not surprising, since OC patients respond almost exclusively to SSRIs and a re duced IMI binding has been related to a positive response to SSRIs [35,36], The specificity of the reduced -^-parox etine binding in OCD is supported by our observation of a negative correlation between symptom severity, as rated by the Y-BOCS total score, and the number of 3H-paroxetine binding sites.…”
Section: Resultsmentioning
confidence: 99%